PENGARUH THINK PAIR SHARE DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR IPAS MELALUI SIKAP TOLERANSI - Sujono, Imam; Nursalim, Nursalim; Sukwatus , Imam (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
This study was motivated by the low IPAS learning outcomes of students at SDN 1 Trenceng Tulungagung, as indicated by the low level of learning mastery (±35%) and the lack of tolerance attitudes in learning interactions. The conventional learning approach that still dominates classroom instruction is considered unable to optimize the achievement of cognitive and social learning objectives. This study aims to analyze the effect of students’ perceptions of the implementation of the Think Pair Share (TPS) learning model and emotional intelligence on IPAS learning outcomes through tolerance attitudes as a mediating variable. This study employed a quantitative approach with an explanatory correlational design. The sample consisted of 59 students determined using the Isaac and Michael formula. Data were collected through Likert-scale questionnaires and documentation of learning outcomes, and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS. The results show that students’ perceptions of the implementation of the TPS model have a positive and significant effect on tolerance attitudes (β = 0.451; t = 4.215; p < 0.001) and learning outcomes (β = 0.312; t = 2.965; p = 0.003). Emotional intelligence also has a significant effect on tolerance attitudes (β = 0.389; t = 3.874; p < 0.001) and learning outcomes (β = 0.330; t = 3.450; p = 0.001). Furthermore, tolerance attitudes significantly affect learning outcomes (β = 0.322; t = 3.102; p = 0.002) and mediate the effects of both variables. The R² values indicate that the model explains 54.2% of the variance in tolerance attitudes and 61.8% of the variance in learning outcomes. Keywords: Think Pair Share, Emotional Intelligence, IPAS Learning Outcomes, Tolerance Attitude